Three-Dimensional Shock Spectrum of Critical Component for Nonlinear Packaging System - Jun Wang; Zhi-Wei Wang; Li-Xin Lu; Yong Zhu; Yong-Guang Wang (Shock and Vibration)
To evaluate the shock characteristics of critical component for a nonlinear packaging system, a new concept of three-dimensional shock spectrum was proposed. Three key coordinate parameters, such as the nondimensional pulse duration, the frequency parameter ratio and the ratio of the maximum response acceleration to the peak pulse acceleration, were governed in a novel dynamical mathematical model. It is shown that the shock response of critical component is weakened owning to the decrease in the defined system parameter. Furthermore, at low frequency parameter ratio, the enhancement of the damping ratio of the critical component leads to the decrease in the peak of the shock response, which can also be reduced by the increase in damping ratio of cushioning pad at both lower and higher frequency parameter ratios. The discussion and analysis provide some insights into the design of cushioning packaging as well.